2019
DOI: 10.11591/ijece.v9i4.pp2703-2714
|View full text |Cite
|
Sign up to set email alerts
|

MHMIC Six-port Interferometer for W-band Transceivers: Design and Characterization

Abstract: The study has presented an extensive analysis of an integrated millimeter wave six-port interferometer, operating over a 10 GHz band, from 80 to 90 GHz. It has covered both semi-unlicensed point-to-point links (81-86 GHz), and imaging sensor system frequencies (above 85 GHz). An in-house process is used to fabricate miniaturized hybrid millimeter wave integrated circuits on a very thin ceramic substrate. Two-port S-parameter measurements are performed on a minimum number of circuits integrated on the same die,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…All unused ports are loaded using integrated resistors of characteristic impedance value. Via-holes are avoided for grounding in order to reduce parasitic elements and to ensure the measurements’ repeatability [ 40 , 83 ]. Broadband RF short circuits implemented with quarter waveguide open stubs are used instead.…”
Section: Circuit and System Characterization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…All unused ports are loaded using integrated resistors of characteristic impedance value. Via-holes are avoided for grounding in order to reduce parasitic elements and to ensure the measurements’ repeatability [ 40 , 83 ]. Broadband RF short circuits implemented with quarter waveguide open stubs are used instead.…”
Section: Circuit and System Characterization Techniquesmentioning
confidence: 99%
“…This works demonstrated that, despite the claims of some experts, microstrip technology can be successfully used at these higher frequencies by appropriate choice of a good quality, very thin substrate, transmission line characteristic impedances, and components’ shape. Authors claimed that, when fabricated in 2014, this was the first MHMIC multi-port operating at more than 80 GHz [ 83 ].…”
Section: Circuit and System Characterization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation